Comparative functional responses of native and high‐impacting invasive fishes: impact predictions for native prey populations. Issue 4 (19th July 2016) - Guo, Zhiqiang; Sheath, Danny; Amat Trigo, Fatima; Britton, J. Robert
Abstract: Comparative functional responses (FRs) can predict impacts of invasive species, including piscivorous fishes, via quantifying their depletion of native food resources as a function of prey density. The utility of FRs for predicting impacts on prey populations by invasive fishes of different trophic guilds was tested here by comparing the FRs of the invaders Cyprinus carpio and Carassius auratus, with three native, trophically analogous fishes, Barbus barbus, Squalius cephalus and Tinca tinca . Chironomid larvae and Gammarus pulex were used as prey items. Predictions, developed from studies on the foraging of C. carpi o and C. auratus in the literature, were that the invaders would have significantly higher consumption rates for chironomids than the native fishes, but not for G. pulex . Mean consumption rates for chironomids were significantly lower for both invaders than B. barbus and S. cephalus, but were similar to T. tinca . Barbus barbus had a significantly lower consumption rate of G. pulex than both invaders, but there were no significant differences between S. cephalus, T. tinca and the invaders. All FRs were type II, with FR curves for the invaders preying upon chironomids never being significantly higher than the native fishes, contrary to predictions. For G. pulex, some significant differences were apparent between the invaders and native fishes, but again were contrary to predictions. These results indicated that when predation impacts of invasive fishes could also be a function of their population density and body sizes, these parameters should be incorporated into FR models to improve impact predictions.